Práticas pedagógicas na educação infantil: um estudo sobre as compreensões de estudantes e profissionais a partir de videogravação - Mello, Simone de (2019)
The following research is inserted in the research line of Knowledge and Development of the Pedagogical Processes of the Graduate Program Master in Education of the Federal University of Fronteira Sul - UFFS and counted on the Capes / FAPESC scholarship. This study is part of a research entitled “Understanding pedagogical practice in early childhood education: second-order observations from video recording”, conducted at an institution in Maceió under the coordination of Lenira Haddad and the consultancy of Danes Hansen; Jensen. This is a pilot study aimed at the appropriation of a method called SOPHOS (Second Order Phenomenological Observation Scheme), developed by two Danish researchers (Hansen; Jensen, 2004) that consists of the observation, by the researcher, of a group of subjects who observe and discuss (in focus groups) two or more videos representing contrasting social practices. In the Brazilian version, two films were made about the daily life of two public schools, one in Maceió, Alagoas, Brazil and another in Aarhus, Denmark. The films last 30 minutes each and the focus group discussions are recorded, transcribed and analyzed according to the adopted theoretical framework. Thus, integrating this international research, this study aims to identify and reflect on the understandings of the pedagogical practice of early childhood education by graduates and professionals graduating from the UFFS Pedagogy course. This study will contribute to international research by enabling triangulation with data obtained in other contexts. It may also be the starting point for future teacher education intervention projects. The study was developed at the Federal University of Fronteira Sul, in the campus located in Chapecó. Three focus groups were conducted, the first consisting of four academic students from the Pedagogy course and members of the Development, Culture and Education research group; the second consisting of five pedagogues graduated from the Pedagogy course, who work with early childhood education and the third group consisting of four academic graduates from the Pedagogy course at the Federal University of Fronteira Sul, in Chapecó who had already attended the internship curriculum component in Children's Education. The focus group discussion was videotaped, transcribed and analyzed with the aid of ATLAS-Ti software, in order to emphasize the comprehension of pedagogical practices related to early childhood education. The most present themes in the groups were grouped into two broad thematic categories: understandings about children and childhood (autonomy, freedom x danger; care) and understandings about the Early Childhood Education Institution (organization of space, time and routine; relationship of institution x role of the teacher, and gender issues). It was found that the Sophos method provided the problematization of crystallized practices in early childhood education, given the strangeness caused by the contrasting practices of the two videos, especially the Danish practices. The focus group dynamics instigated reflections that led to small changes in the participants' understanding of the topics addressed. It is expected that the study will contribute to raise quality indicators for the Pedagogy course at the Federal University of Fronteira Sul, in the campus of Chapecó, regarding the pedagogical practices in early childhood education, as the subjects involved are graduates and graduating students of this course.